DNA Damage and Inhibition of Akt Pathway in MCF-7 Cells and Ehrlich Tumor in Mice Treated with 1, 4-Naphthoquinones in Combination with Ascorbate. (22nd February 2015) - Ourique, Fabiana; Kviecinski, Maicon R.; Felipe, Karina B.; Correia, João Francisco Gomes; Farias, Mirelle S.; Castro, Luiza S. E. P. W.; Grinevicius, Valdelúcia M. A. S.; Valderrama, Jaime; Rios, David; Benites, Julio; Buc Calderon, Pedro; Pedrosa, Rozangela Curi
Abstract : The aim of this study was to enhance the understanding of the antitumor mechanism of 1, 4-naphthoquinones and ascorbate. Juglone, phenylaminonaphthoquinone-7, and 9 (Q7/Q9) were evaluated for effects on CT-DNA and DNA of cancer cells. Evaluations in MCF-7 cells are DNA damage, ROS levels, viability, and proliferation. Proteins from MCF-7 lysates were immunoblotted for verifying PARP integrity, γ H2AX, and pAkt. Antitumor activity was measured in Ehrlich ascites carcinoma-bearing mice. The same markers of molecular toxicity were assessed in vivo . The naphthoquinones intercalate into CT-DNA and caused oxidative cleavage, which is increased in the presence of ascorbate. Treatments caused DNA damage and reduced viability and proliferation of MCF-7 cells. Effects were potentiated by ascorbate. No PARP cleavage was observed. Naphthoquinones, combined with ascorbate, caused phosphorylation of H2AX and inhibited pAkt. ROS were enhanced in MCF-7 cells, particularly by the juglone and Q7 plus ascorbate. Ehrlich carcinoma was inhibited by juglone, Q7, or Q9, but the potentiating effect of ascorbate was reproduced in vivo only in the cases of juglone and Q7, which caused up to 60% inhibition of tumor and the largest extension of survival. Juglone and Q7 plus ascorbate caused enhanced ROS and DNA damage and inhibited pAkt also in Ehrlich carcinoma cells.